(untitled) (Research, Society and Development, 2021)
Virtual Learning Environments (VAS) are increasingly present in educational institutions due to the fact that such systems represent another resource for improving communication between students and professors. Although these systems are not new, there are few studies evaluating their performance as well as the decurrent energy consumption. Assessing the relationship between AVA’s performance and energy consumption is critical to solving problems in the initial phases of new projects or during the upgrading of existing infrastructure. Therefore, this work aims to evaluate the performance and power consumption of the Moodle environment, a platform that provides AVAs support, using two private cloud systems, Apache CloudStack and OpenStack. In order to accomplish this, a methodology is adopted to support the evaluation of such experiments. Additionally, case studies have been conducted to illustrate the applicability of the methodology assuming the private clouds Apache CloudStack and OpenStack. The results revealed that performance and also energy consumption are different between the two systems. For example, in the experiments performed, OpenStack showed a higher power consumption when compared to the Apache CloudStack because it demands a longer response time.